2016
DOI: 10.3747/co.23.3140
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Cancer Survivors While Transitioning from Tertiary to Primary Care

Abstract: PurposeIn current fiscally constrained health care systems, the transition of cancer survivors to primary care from tertiary care settings is becoming more common and necessary. The purpose of our study was to explore the experiences of survivors who are transitioning from tertiary to primary care. MethodsOne focus group and ten individual telephone interviews were conducted. Data saturation was reached with 13 participants. All sessions were audio-recorded, transcribed verbatim, and analyzed using a qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…In some cases, HRQOL may be too distal an outcome in RCTs of SCPs’ effectiveness [36]. Stakeholders in this study identified more proximal outcomes (e.g., capacity for self-management, sense of control), which are consistent with themes identified in a study characterizing transitional readiness among survivors [37]. By assessing distal outcomes, RCTs may burden stakeholders by collecting data on outcomes not directly influenced by SCPs.…”
Section: Discussionsupporting
confidence: 62%
“…In some cases, HRQOL may be too distal an outcome in RCTs of SCPs’ effectiveness [36]. Stakeholders in this study identified more proximal outcomes (e.g., capacity for self-management, sense of control), which are consistent with themes identified in a study characterizing transitional readiness among survivors [37]. By assessing distal outcomes, RCTs may burden stakeholders by collecting data on outcomes not directly influenced by SCPs.…”
Section: Discussionsupporting
confidence: 62%
“…Problems with communication between oncology and primary care teams, as well as the absence of clear directives on survivor care, can limit coordination of care, 35 , 39 – 41 transition of routine follow-up care, 24 , 42 feeling able to trust family physicians to play a more active role with this clientele, 43 and survivors having confidence in their primary care team to follow-up posttreatment. 1 , 44 , 45 Also, these difficulties about coordinating care between primary care and specialized care seem recurrent in the general practice. 46 In addition, in terms of social context, participants perceived survivors’ difficulty with obtaining ongoing accommodations in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…A reliance on hospital‐based, specialist‐led follow‐up is not ideal, with a lack of resources prompting transition of lower‐risk survivors to follow‐up in primary care . For many survivors, there are advantages to being transitioned to primary care.…”
Section: Introductionmentioning
confidence: 99%